Antibiotics Prophylaxis for Operative Hysteroscopy: A Multicenter Randomized Controlled Clinical Study. (April 2017) - Muzii, Ludovico; Di Donato, Violante; Boni, Terenzio; Gaglione, Raffaele; Marana, Riccardo; Mazzon, Ivan; Imperiale, Ludovica; De Medici, Caterina; Ruggiero, Alfonso; Panici, Pierluigi Benedetti
Objective: To evaluate the incidence of infectious complications and effect of prophylactic antibiotic administration during operative hysteroscopic procedures. Methods: A multicentric randomized controlled trial was conducted between January 2012 and December 2013. Women (n = 180) affected by endometrial hyperplasia, myomas, or endometrial polyps undergoing operative hysteroscopy were randomized to receive cefazolin 2 g intravenously 30 minutes prior to the procedure (n = 91) and no treatment (n = 89). Results: No statistical difference in terms of postoperative fever (2.4% vs 2.3%, P = .99), endometritis (0% vs 0%), pain (6.0% vs 10.4%, P = .40), cervicitis–vaginitis (0% vs 0%), pelvic abscess (0% vs 0%), pelvic inflammatory disease (0% vs 0%), and bleeding (0% vs 0%) was noticed. No statistical difference in terms of side effects attributable to antibiotic prophylaxis such as allergy (0% vs 4.8%, P = .12), nausea (10.7% vs 17.4%, P = .27), vomiting (3.6% vs 4.6%, P = .99), diarrhea (4.8% vs 5.4%, P = .99), cephalea (9.5% vs 3.5%, P = .13), dizziness (4.8% vs 2.3%, P = .44), and meteorism (5.4% vs 3.4%, P = .99) was noticed. Conclusion: The results of the current study support the recommendation not to prescribe routine antibiotic prophylaxis prior to operative hysteroscopy.